Young Firms and Monetary Policy Transmission. (IMF Working Papers; Working Paper, 2021)
We investigate the role of business dynamism in the transmission of monetary policy by exploitingthe variation in firm demographics across U.S. states. Using local projections, we find that a larger fraction of young firms significantly mutes the effects of monetary policy on the labor market and personal income over the medium term. The firm entry rate and the employment share of young firms are key factors underpinning these results, which are robust to a battery of robustness tests. We develop a heterogeneous-firm model with age-dependent financial frictions that rationalizes the empirical evidence.